Molecular abnormality of phosphoglycerate kinase-Uppsala associated with chronic nonspherocytic hemolytic anemia. - Fujii, H (1980)
Inherited deficiency of phosphoglycerate kinase (PGK; ATP:3-phosphoglycerate 1-phosphotransferase, EC 2.7.2.3) is associated with chronic nonspherocytic hemolytic anemia and mental disorders in man. One such variant, PGK-Uppsala, was purified to homogeneity. PGK-Uppsala had a lower-than-normal specific activity (30% of normal in the backward reaction and about 20% of normal in the forward reaction) and higher-than-normal Michaelis constants for ATP, ADP, 3-phosphoglycerate and 1,3-diphosphoglycerate. Peptide mapping analysis revealed that the structural abnormality of PGK-Uppsala is a single amino acid substitution from arginine to proline at the 206th position. Based on the known complete amino acid sequence of the normal human PGK and the three-dimensional model deduced from horse PGK, correlations between the structural and functional abnormalities of PGK-Uppsala are discussed. Structural abnormalities of PGK-II, which is an electrophoretic variant not associated with enzyme deficiency, and PGK-München, which is associated with enzyme deficiency and heat instability but not associated with hemolytic anemia, are also discussed.